How Political is the Personal? Notes on Gender and Domestic Violence against Women. - Pozo Gándara, Concepción (Investigaciones Feministas (Feminist Research), 2013)
In studies on domestic violence against women attention to subjective experiences of women has resulted in scientific discourses and social practices and interventions. In this essay we move beyond the notion of patriarchy by including in our study of violence concepts of the social sciences that conceptualize gender as a relational and historical category that operates through the intersection of other categories. To achieve this aim, we analyze the interviews of eighteen men and seventeen women involved with Brazilian laws that regulate crimes of violence against women. We identify and discuss some topics such as victimization, the report of an aggression, and the process of escaping a violent relationship.
Keywords: violence against women; gender relations; victimization; denunciation